Tahkrij and Syarah Hadith Agrotechnology Black Cumin Plants as Natural Medicines to Treat Acne - Putri Napisah; Wahyudin Darmalaksana; Cecep Hidayat (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to discuss the hadith of the Prophet Muhammad about the black cumin plant. This research method is qualitative through the tahkrij and sharah hadith approaches with agrotechnological analysis. The results and discussion of this study is that black cumin plant is a natural remedy for treating acne. This research shows that acne treatment with black cumin does not cause side effects.